Fiqh al-Bi’ah: Kontribusi Pemikiran Yusuf al-Qaradawi terhadap Pelestarian Lingkungan - Muhamad Saefullah (Ma'had Aly Journal of Islamic Studies, 2026)
The escalating global ecological crisis demands a formulation of Islamic law capable of responding to environmental issues in both normative and contextual ways. This article examines the contribution of the fiqh al-bi’ah thought of Yusuf al-Qaradawi in Ri‘ayah al-Bi’ah fi Syari‘at al-Islam to environmental preservation and the realization of public welfare within the context of the modern ecological crisis, employing a qualitative approach through library research and descriptive-analytical methods. The study argues that al-Qaradawi reconstructs Islamic law by positioning environmental issues as an integral part of maqaṣid al-shari‘ah, grounded in the principles of tawḥid (divine unity), the trust of human vicegerency (khilafah), and the legal maxim of preventing harm. The environment is thus understood not merely as an object of exploitation, but as a divine trust encompassing moral, legal, and spiritual dimensions. By expanding the meaning of fasad (corruption or destruction) to include contemporary ecological damage and elevating environmental preservation to the level of a legal obligation as well as an act of worship, al-Qaradawi proposes an ecological, contextual, and intergenerationally just paradigm of Islamic jurisprudence. This study demonstrates that fiqh al-bi’ah serves as a normative and strategic instrument for building a sustainable Islamic civilization oriented toward the realization of public welfare